2009
DOI: 10.1111/j.1742-4658.2009.06996.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural features and dynamics of a cold‐adapted alkaline phosphatase studied by EPR spectroscopy

Abstract: EPR spectroscopy, performed after site‐directed spin‐labeling, was used to study structural dynamics in a cold‐adapted alkaline phosphatase (EC 3.1.1.1). Differences in the structural environment of six spin‐labeled side chains allowed them to be classified (with reference to previously obtained mobility maps) as belonging to loop positions (either relatively surface exposed or in structural contact) or helix positions (surface exposed, in contact, or buried). The mobility map constructed in the present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Techniques that provide a relative estimation of structural flexibility exist, but they in several cases do not directly measure flexibility, but some properties correlated to it, as relative resistance to proteolysis [94][95][96], fluorescence of tryptophan or tyrosine residues [97][98][99][100], hydrogen/deuterium (H/D) exchange experiments monitored by NMR [101,102], Fourier Transform Infrared Spectroscopy (FT-IR) [103,104] or ElectroSpray Ionization-Mass Spectrometry (ESI-MS) [105,106], experiments with fluorescent ANS dye , Electron Paramagnetic Resonance (EPR) [108][109][110], Single Molecule Foster Resonance Energy Transfer (FRET) [111]. Therefore, these techniques are often unable to identify specific but relevant regions of localized flexibility, because their estimations describe, in many cases and with few exceptions, overall properties.…”
Section: Experimental Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Techniques that provide a relative estimation of structural flexibility exist, but they in several cases do not directly measure flexibility, but some properties correlated to it, as relative resistance to proteolysis [94][95][96], fluorescence of tryptophan or tyrosine residues [97][98][99][100], hydrogen/deuterium (H/D) exchange experiments monitored by NMR [101,102], Fourier Transform Infrared Spectroscopy (FT-IR) [103,104] or ElectroSpray Ionization-Mass Spectrometry (ESI-MS) [105,106], experiments with fluorescent ANS dye , Electron Paramagnetic Resonance (EPR) [108][109][110], Single Molecule Foster Resonance Energy Transfer (FRET) [111]. Therefore, these techniques are often unable to identify specific but relevant regions of localized flexibility, because their estimations describe, in many cases and with few exceptions, overall properties.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…A cysteine side chain is introduced into the protein structure with site-directed mutagenesis, or free cysteine residues already available are employed, and they are subsequently chemically modified. EPR spectroscopy, performed after site-directed spin-labeling, mutating serine residues to cysteine, was used to study structural dynamics in a cold-adapted alkaline phosphatase (EC 3.1.1.1) and on its mutant variants in the proximity of the active-site [108]. Differences in the structural environments of six spin labels allowed them to be classified to specific secondary structural elements and to define the degree of contacts and the solvent accessibility, according to mobility maps.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…Single structural effects cannot be easily estimated if significant differences in the protein architecture are found. Recently, several comparative approaches of homologs adapted to different temperature conditions but belonging to the same enzymatic family (Cartier et al, 2010;Coquelle et al, 2007;Khan and Sylte, 2009;Papaleo et al, 2008;Siglioccolo et al, 2010) have been successfully applied, along with comparison of protein dynamic properties of extremophilic homologs Chiuri et al, 2009;D'Auria et al, 2009;Heidarsson et al, 2009;Kundu and Roy, 2009;Mereghetti et al, 2010;Papaleo et al, 2006;Pasi et al, 2009) to disclose structure-function relationships in cold-and warm-adapted enzymes. Most of these studies compared mesophilic and psychrophilic enzymes, since few cases are known for which enzymes with know 3D structure are available along the whole scale of temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously observed that the exchange of Cys for residues at various sites in VAP decreased the activity of the enzyme substantially . Here, all of the Cys replacements decreased the k cat and most of the substitution increased the K M (Table S2).…”
Section: Resultsmentioning
confidence: 59%